2021
DOI: 10.1039/d1cp02015c
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanohorns as nanocontainers for cisplatin: insight into their interaction with the plasma membranes of normal and breast cancer cells

Abstract: Cisplatin (cddp)-based chemotherapy is one of the most effective therapeutic alternatives for breast cancer treatment, the most common form of cancer, despite the severe side effects related to the high...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(27 citation statements)
references
References 67 publications
7
20
0
Order By: Relevance
“…This behavior reflects a reduction in the number of interactions between the drugs and the nanocarrier in the adsorbed formulations. Moreover, the drug–CNHox pair energies are mainly composed of vdw interactions, as we also concluded for the 3cddp@CNHox complex . Recently, Mejri et al reported a pair energy value of −80.0 kcal mol –1 for an inclusion complex formed by four cddp molecules encapsulated into a hydroxyl-terminated CNT (4cddp@CNT in our notation).…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…This behavior reflects a reduction in the number of interactions between the drugs and the nanocarrier in the adsorbed formulations. Moreover, the drug–CNHox pair energies are mainly composed of vdw interactions, as we also concluded for the 3cddp@CNHox complex . Recently, Mejri et al reported a pair energy value of −80.0 kcal mol –1 for an inclusion complex formed by four cddp molecules encapsulated into a hydroxyl-terminated CNT (4cddp@CNT in our notation).…”
Section: Resultssupporting
confidence: 81%
“…Overall, the negative values of the free energies shown in Table indicate that the CNHox model forms stable complexes with cddp, as we recently reported it, and cpx and oxa. This behavior is also graphically represented by the green bars in Figure .…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations